RhoA, RhoB and RhoC differentially regulate endothelial barrier function - Pronk, Manon C. A. (Small GTPases, 2017)
RhoGTPases are known regulators of intracellular actin dynamics that are important for maintaining endothelial barrier function. RhoA is most extensively studied as a key regulator of endothelial barrier function, however the function of the 2 highly homologous family-members (> 88%) RhoB and RhoC in endothelial barrier function is still poorly understood. This study aimed to determine whether RhoA, RhoB and RhoC have overlapping or distinct roles in barrier function and permeability in resting and activated endothelium. By using primary endothelial cells in combination with siRNA transfection to establish individual, double or triple knockdown of the RhoA/B/C RhoGTPases, we found that RhoB, but not RhoA or RhoC, is in resting endothelium a negative regulator of permeability. Loss of RhoB accounted for an accumulation of VE-cadherin at cell-cell contacts. Thrombin-induced loss of endothelial integrity is mediated primarily by RhoA and RhoB. Combined loss of RhoA/B showed decreased phosphorylation of Myosin Light Chain and increased expression of VE-cadherin at cell-cell contacts after thrombin stimulation. RhoC contributes to the Rac1-dependent restoration of endothelial barrier function. In summary, this study shows that these highly homologous RhoGTPases differentially control the dynamics of endothelial barrier function.